2017
DOI: 10.3892/or.2017.5874
|View full text |Cite
|
Sign up to set email alerts
|

Benzo(a)pyrene enhances the EMT-associated migration of lung adenocarcinoma A549 cells by upregulating Twist1

Abstract: Benzo(a)pyrene (BaP), an important toxic component of cigarette smoke, can cause lung cancer and lead to the progression of lung cancer. In the present study, we investigated the effect of BaP on the migration of lung adenocarcinoma A549 cells. BaP (1 µM) promoted the migration of A549 cells in a time-dependent manner and upregulated the expression of the Twist family BHLH transcription factor 1 (Twist1). BaP also induced upregulation of the mesenchymal markers N-cadherin and vimentin and downregulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…E-cadherin, a member of the cadherin family of cell adhesion molecules, is an important intercellular adhesion molecule and is now recognized as a cancer metastasis suppressor molecule (when E-cadherin expression is reduced, tumors are more likely to metastasize) ( 25 ). Twist1, a apoptosis inhibitor protein found in recent ten years, is an important regulatory factor in the development of malignant tumor cells and EMT ( 24 ). ZEB (zinc finger E-boxbinding homeobox) is an important transcription factor whose family members include ZEB1 and ZEB2, which are important condition factors for EMT ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-cadherin, a member of the cadherin family of cell adhesion molecules, is an important intercellular adhesion molecule and is now recognized as a cancer metastasis suppressor molecule (when E-cadherin expression is reduced, tumors are more likely to metastasize) ( 25 ). Twist1, a apoptosis inhibitor protein found in recent ten years, is an important regulatory factor in the development of malignant tumor cells and EMT ( 24 ). ZEB (zinc finger E-boxbinding homeobox) is an important transcription factor whose family members include ZEB1 and ZEB2, which are important condition factors for EMT ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is an important regulatory transcription factor in the process of embryonic development. Twist is involved in the growth and development of normal organs, and it is also an important regulator of EMT in malignant tumor cells ( 24 ). E-cadherin, a member of the family of cadherin proteins in cell adhesion molecules, is an important intercellular adhesion molecule and epithelial phenotype that has been recognized as a suppressor of cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Bleomycin treatments on A549 cells for 4 days reduced the expression of E-cadherin by stimulating the TGF-β/ Smad3 signalling pathway, while it induced α-SMA and vimentin expressions. A549 cells differentiate into myofibroblasts by EMT activation [27]. Many studies report that when A549 cells are stimulated with TGF-β, the cells begin to produce mesenchymal cell proteins such as vimentin, desmin, N-cadherin, α-SMA, fibronectin and collagen instead of epithelial cell markers such as Ecadherin, cytokeratin and zonula okludens-1.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on the alterations of EMT markers in lung cancer demonstrated that decreased E-cadherin or increased fibronectin levels are associated with poor survival outcomes. [ 47 ] Inhibition of tumor invasion or migration is one of the goals of suppressing CSC properties, especially in patients who have metastases instead of only a primary lesion. The results of Boyden chamber assays showed the enhancement of the long-term effects of combined NNK and arecoline exposure on SCC25 and FaDu cell motility and migration, which are integral steps in the metastatic cascade of tumor cells, suggesting that long-term exposure to NNK and arecoline can promote invasion and metastasis to distal sites.…”
Section: Discussionmentioning
confidence: 99%